STATUS OF HEALTH IN THE REGIONS OF SIBERIA AND THE FULFILLMENT OF THE MESSAGE OF THE PRESIDENT OF THE RUSSIAN FEDERATION TO THE FEDERAL ASSEMBLY OF THE RUSSIAN FEDERATION FROM DECEMBER 12, 2013 - L. S. Shalygina; M. F. Sadovoy; Ye. A. Finchenko; Ye. V. Mamonova; I. A. Tsytsorina (Бюллетень сибирской медицины, 2014)
The aim of the study was to identify the key problems of regional health services in the Siberian Federal district and justification of the priority directions of their decision. For the first time using the method of expert estimations conducted a study of health problems in the Federal district, identified key issues, as well as justifies the priority directions of their decisions. The study was conducted on the basis of statistical materials of the health authorities of the regions of Siberian Federal district, as well as expert assessments. Identified key health issues and priorities of their decision. Based on the systematic work of the expert community and across government levels defined key for the regions of Siberia health problems and justify the priority directions of their solutions tailored to focus efforts in the social sphere, which will allow to coordinate policies in the health sector on the territory of the Siberian Federal district, which in turn, will increase its effectiveness.